Moral judgment and environmental attitude of fifth grade high school students from Barranco - Chumbe, Aldo (2011)
The main objective of this research is to determine whether there is a significant relationship between moral judgments and environmental attitude, according to the type of educational management, gender and age. Correlational design is used. The representative sample consists of 238 fifth grade students of secondary education Barranco district of Lima. Instruments are applied: Socio Moral Reflection Questionnaire (SROM) and Environmental Attitude Scale (ESACAMB). Data analysis is developed using SPSS 15.0 statistical and the Pearson's r, chi-square, Student t test and ANOVA. We conclude that there is significant correlation between moral judgments and environmental attitude. With regard to moral judgments, students are placed in the third stage of Kohlberg's theory, the students of non-state schools demonstrate greater moral judgments state students, no significant differences by gender or age. Regarding the environmental attitude, students are placed at a high level, with women significantly outperform men, and there are no significant differences according to type of educational management or age.